(3GdOdjd GdTGaj Ydi Gdefgd GdUGais - (3jhSa Hf JZQj HQOj Hf YHO Gddg GdXGgQj GdMfaj, CHh GdeMGSf , GHf JZQj HQOj , LeGd GdOjf, J (B874 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi dG jSJOd Ydjg EdG Hg s
(3BNQgG (B:s
(3hgh dG jNd Yf GdJGQjN GdePchQ HJQLeI hGMOI s
(3hQJHg Ydi JQJHg ef Chdg Edi BNQg hGNJUQJ ajg GdJQGLe LOkG djchf GdfGXQ ai Pdc Ydi HUjQIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B222 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B282s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B134 s
Keywords: (3GdJGQjNs